O projeto político-pedagógico do curso de Medicina da Unioeste – Francisco Beltrão: um estudo a partir das diretrizes nacionais curriculares de 2001 - Kussakawa, Diogo Hiroshi Beçon (2018)
The medical education in Brazil is pointed for several social agents as a fundamental factor to complete the transformation of country health care sector reality. The National Curricular Guidelines for undergraduate courses of Medicine, promoted in November 7th 2001 – NCG 2001, represent curricular reform proposals materialized in laws. The form how NCG are interpreted and executed, manifested as political-pedagogic projects – PPP, may vary according to social collective they impact. The main research question is to understand how curricular reform proposals, materialized in NCG 2001, reached undergraduate course of UNIOESTE – campus Francisco Beltrão, through PPP analysis. Specific objectives are demonstration of Brazil’s medical education historical development, from constitutive movements of medical practice, public health and college educational policies; pointing of advances and setbacks of medical formation process found by curricular reforms debaters in the model before NCG 2001, and explanation of rupture proposals from that model, as well as implantation and evaluation of transitional strategies. Methodology employed was documental research, through content analysis of NCG 2001 resolutions and PPP of UNIOESTE Medicine undergraduate course. Results concluded that documents are oriented by three types of referential categories: philosophic-conceptual, methodologic and technical-administrative. Philosophicconceptual references are structural axis determined by influence’s areas from several knowledge sources. Health promotion axis corresponds to the health conception changes, with emphasis in collective health and social health determinants. Political-economic axis corresponds to needs of manager concept of future doctor, considering risks, benefits, resources, learning-in-job and competences. Ethical-cultural axis correlates with ability of future doctor to communicate with several cultural groups, respecting the equity and autonomy principles. Symbolic-technologic axis corresponds to symbolic control, from results and goals implicit charging, through reports and computational index. Methodologic references correspond to competency-based curriculum and active learning methodologies. Technical-administrative references are instructions to regulate pedagogic work in course. The study concluded to existence of agreement between curricular reform proposals by NCG 2001 and way chosen by UNIOESTE Medicine undergraduate course.